Analisis Yuridis Kekuatan Hukum Sertifikat Hak Milik Atas Tanah Menurut Peraturan Pemerintah No. 24/1997 Tentang Pendaftaran Tanah Dikaitkan Dengan Putusan PN No. 242/Pdt.G/2020/PN Ambon - Semuel Nahumury; Jenny Kristiana Matuankotta; Pieter Radjawane (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The certificate is proof of the rights owned by the holder of land rights issued by the National Land Agency. Issuance of certificates in the context of land registration activities so that rights holders can make certificates as evidence to holders of land rights as regulated in Government Regulation no. 24 of 1997 concerning Land Registration.Purposes of the Research: This study examines the ratio decidendi of judges in making decisions on the PN No. 242/Pdt.G/2020/PN.Amb regarding the validity of the certificate of title to land to determine whether the judge's considerations are in accordance with the legal provisions regarding the ownership of applicable land rights. Methods of the Research: The research method used is normative research through a statutory approach and a case approach which refers to the ratio decidendi. The method of collecting legal materials used is a qualitative method.Results of the Research: Based on the results of the study, evidence has an important role as the basis for judge's consideration in making a decision. Certificates as evidence of rights can be declared invalid and canceled by a court decision that has permanent legal force when it is proven that someone's ownership of land rights has been violated. In the decision of the PN No. 242/Pdt.G/2020/PN Ambon, the judge ruled that the certificate owned by the defendant was legally flawed and had no binding legal force because the defendant could not prove the formal or material truth of the acquisition of the land rights.